Effects of melatonin on cadmium accumulation in the accumulator plant Perilla frutescens. Issue 6 (3rd July 2019) - Xiang, Gang; Lin, Lijin; Liao, Ming'an; Tang, Yi; Liang, Dong; Xia, Hui; Wang, Jin; Wang, Xun; Sun, Guochao; Zhang, Huifen; Zou, Yao; Ren, Wei
ABSTRACT: To enhance the phytoremediation ability of the heavy metal accumulator Perilla frutescens, melatonin (MT) was applied at different concentrations (0, 25, 50, 100, 150, and 200 μmol/L) to P. frutescens growing in cadmium (Cd) contaminated soil (10 mg/kg). The MT treatments increased the root and shoot biomasses of P. frutescens, with the maximum increase in the 150 μmol/L MT treatment (79.51% and 36.18% higher, respectively, than those of the control). The MT treatments also enhanced superoxide dismutase activity, peroxidase activity, and the soluble protein concentration of P. frutescens, and 100–200 μmol/L MT increased the chlorophyll a, chlorophyll b, and total chlorophyll concentrations in P. frutescens . The MT treatments increased the Cd concentrations in roots and shoots of P. frutescens in a dose-dependent manner. Different MT concentrations increased the Cd accumulation amounts of roots and shoots of P. frutescens, with the maxima accumulation amounts in the 150 μmol/L MT treatment (226.98% and 85.89% higher, respectively, than those of the control). These results show that MT can promote the growth and phytoremediation ability of P. frutescens growing in Cd-contaminated soil, and the optimum MT dose is 150 μmol/L.